Defining the role of natural killer cells in acute myeloid leukemia through the lens of single-cell omics - Liang, Chen; Yue, Meichi; Zhang, Kehui; Zhou, Sining; Xu, Xiaojing; Wang, Shiwei; Liu, Shiping (Frontiers in Immunology, 2026)
This review explores the alterations in natural killer (NK) cell function in acute myeloid leukemia (AML) and their implications for disease progression and therapeutic outcomes. As key effectors of innate immunity, NK cells are critical in recognizing and eliminating malignant cells. In AML, however, NK cells frequently exhibit numerical and functional deficiencies, resulting in compromised immunosurveillance that facilitates tumor immune escape and disease advancement. We systematically examine the application of single-cell omics technologies in AML research to elucidate the omics profiles and phenotypic distribution of NK cells within the leukemic microenvironment, characterizing their dysfunctional state by upregulated inhibitory receptors, downregulated activating signals, an altered cytokine milieu, and complex cellular crosstalk within the bone marrow (BM) niche. Furthermore, this article correlates functional dynamics of NK cells with conventional and emerging treatments, including CAR-NK immunotherapy, underscoring their potential role in disease monitoring and prognostic stratification. We also discuss promising NK cell-based immunotherapeutic strategies for AML, emphasizing the potential of modulating or engineering NK cells to enhance antitumor immunity. A deeper understanding of NK cell biology and regulatory mechanisms in AML is essential for developing novel immunotherapies and improving patient prognosis.